The virtual battlefield : perspectives on cyber warfare - Czosseck, Christian; Geers, Kenneth (Cryptology and information security series ;, 2009)
"All political and military conflicts now have a cyber dimension, the size and impact of which are difficult to predict. Internet-enabled propaganda, espionage, and attacks on critical infrastructure can target decision makers, weapons systems, and citizens in general, during times of peace or war. Traditional threats to national security now have a digital delivery mechanism which would increase the speed, diffusion, and power of an attack. There have been no true cyber wars to date, but cyber battles of great consequence are easy to find. This book is divided into two sections - Strategic Viewpoints and Technical Challenges & Solutions - and highlights the growing connection between computer security and national security"--Jacket.